Improving patient care: the implementation of change in health care - Wensing, Michel; Grol, Richard; Grimshaw, Jeremy (John Wiley & Sons, 2020)
Implementation of change in healthcare : a complex problem / Richard Grol, Michel Wensing -- Theories on implementation of change in healthcare / Michel Wensing, Richard Grol -- Effective implementation of change in healthcare : a systematic approach / Richard Grol, Michel Wensing -- Planning and organizing the change process / Richard Grol, Michel Wensing -- Characteristics of successful innovations / Richard Grol, Michel Wensing -- Clinical practice guidelines as a tool for improving patient care / Jako Burgers, Trudy van der Weijden, Richard Grol -- Indicators for quality and safety of care / Jozé Braspenning, Rosella Hermens, Hilly Calsbeek, Stephen Campbell, Philip van der Wees, Richard Grol -- Determinants of implementation / Michel Wensing, Richard Grol -- Methods to identify and analyze determinants of implementation / Michel Wensing, Richard Grol -- Selection of strategies for improving patient care / Richard Grol, Michel Wensing -- Dissemination of innovations / Richard Grol, Michel Wensing -- Educational implementation strategies / Michel Wensing, Cornelia Fluit, Jeremy Grimshaw, Richard Grol -- Clinical performance feedback and decision support / Noah Ivers, Benjamin Brown, Jeremy Grimshaw -- Engaging patients in healthcare improvement and innovation / Glyn Elwyn, Amy Price -- Organizational implementation strategies / Michel Wensing, Miranda Laurant, Richard Grol -- Patient safety strategies / Marieke Zegers, Mirelle Hanskamp-Sebregts, Hub Wollersheim, Charles Vincent -- Health system strategies for implementation / Michel Wensing, Holger Pfaff, Richard Grol -- Multifaceted implementation strategies / Marlies Hulscher, Michel Wensing -- Planning of implementation / Richard Grol -- Experimental designs for evaluation of implementation strategies / Michel Wensing, Jeremy Grimshaw -- Observational evaluation of implementation strategies / Michel Wensing, Jeremy Grimshaw -- Process evaluation of implementation strategies / Marlies Hulscher, Michel Wensing -- Economic evaluation of implementation strategies / Johan L. Severens, Ties Hoomans, Eddy Adang, Michel Wensing.